Tinjauan Literatur Efektivitas Pembelajaran Daring Sinkron dan Asinkron serta Peran Supervisi Daring dalam Pendidikan - Nurlaila Nurlaila; Ismawati Ismawati; Fitriati Fitriati; Marnita Marnita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Digital transformation in education has encouraged the widespread implementation of online learning; however, its practice still faces several challenges, including limited learning interaction, a lack of flexibility in learning models, insufficient teacher digital competencies, and suboptimal technology-based academic supervision. These conditions require an effective and sustainable digital learning model. This study aims to analyze the effectiveness of synchronous and asynchronous online learning and to examine the role of online supervision in improving learning quality. The study employed a qualitative approach using a Systematic Literature Review (SLR) design. Data were collected from various academic databases and analyzed through data reduction, categorization, comparison, and synthesis techniques. The findings indicate that synchronous learning is more effective in enhancing interaction, motivation, and student engagement through direct communication and immediate feedback. Meanwhile, asynchronous learning is superior in providing time flexibility, repeated access to learning materials, and fostering independent learning. In addition, online supervision plays an important role in maintaining learning quality through monitoring, evaluation, mentoring, and improving teachers’ competencies. The integration of synchronous learning, asynchronous learning, and online supervision is the most relevant approach to creating an effective, adaptive, inclusive, and sustainable digital learning system.